Optimisation studies on inclined web wheel using finite elements - Jayaprakash, V.; Ng, Gheok Kuan (Faculty of Mechanical Engineering, 1998)
The optimisation studies on wheels have generated much interest among the researchers in order to upgrade the wheel performance. Wheels find application as wheel in automobiles, trains, as pulleys, helical gears etc. Optimum shape of wheel is the fundamental objective of designers. Finite Element Method (FEM) is an appropriate technique suitable for computer implementation. This study is mainly concerned about the analysis of stress and deflection of the web of wheel under static loading conditions. Modification of geometric parameters such as web inclination, fillet radius and rim-volume reduce the stress distribution and deflection of wheel axial loading condition. The investigation reveals information on shape optimisation and the resulting stress reduction.